The Impact of Customer Online Reviews on Purchase Decision in Vietnam: Using Brand Switching as A Mediator - Nguyen, Thanh Lam; Dat, Nguyen Thanh (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2024)
The rapid development of technology leads to diversification in consumer behavior. Businesses face greater competition challenges. New factors such as online customer reviews also affect consumer purchasing decisions. In order to create sustainable sales growth, businesses need to pay attention to the customer experience to reduce the percentage of customers switching to a new brand. This study incorporates these factors into the proposed model to assess their relationship. The analytical results show that the factors of customer online reviews and brand switching all impact purchase decisions.. Research is meant for businesses in general and marketers in particularly.